The Influence of Workload, Work Motivation, and Organizational Citizenship Behavior on Job Satisfaction inPT Pertamina (Persero) Refinery Unit (Ru) VI Balongan - Selfi Yuliani; Afwa Afiah; Siti Maryam (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This research is motivated by the importance of increasing employee job satisfaction, because currently there are many problems that can affect job satisfaction such as workload that exceeds capacity or ability, low work motivation and suboptimal performance, and the need for organizational citizenship behavior in supporting company quality. By understanding the relationship between these three factors, companies can create more effective strategies, appropriate policies, and ideal work procedures so that optimal job satisfaction can be achieved. This study reveals the influence of workload, work motivation, and Organizational Citizenship Behavior (OCB) on job satisfaction.